2018
DOI: 10.3389/fnmol.2018.00422
|View full text |Cite
|
Sign up to set email alerts
|

Contactin-1/F3 Regulates Neuronal Migration and Morphogenesis Through Modulating RhoA Activity

Abstract: During neocortical development, newborn neurons migrate along radial fibers from the germinal ventricular zone (VZ) toward the cortical plate (CP) to populate the cerebral cortex. This radial migration requires adhesion activities between neurons and radial fibers; however, past research has identified only a limited number of adhesion molecules involved in this process. Contactin-1/F3 (Cntn1), a cell adhesion molecule expressed in the developing nervous system is essential for many key developmental events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 73 publications
3
22
0
Order By: Relevance
“…To directly monitor the effects of BicD2 K775X variant on neuronal migration, we employed time-lapse imaging of neurons in live embryonic brain slices [8,9,49]. Brains electroporated with BicD2 WT or K775X at E14.5 were sliced and cultured at E17.5.…”
Section: Bicd2 K775x Impaired Neuronal Migration and Nucleuscentrosommentioning
confidence: 99%
See 1 more Smart Citation
“…To directly monitor the effects of BicD2 K775X variant on neuronal migration, we employed time-lapse imaging of neurons in live embryonic brain slices [8,9,49]. Brains electroporated with BicD2 WT or K775X at E14.5 were sliced and cultured at E17.5.…”
Section: Bicd2 K775x Impaired Neuronal Migration and Nucleuscentrosommentioning
confidence: 99%
“…The live brain slice imaging was performed as previous described [8,9,51]. Briefly, live mouse brains were coronal sectioned into 350 μm-thick slices using the Vibratome (Leica) 2.5 days after electroporation.…”
Section: Live Brain Slice Imagingmentioning
confidence: 99%
“…In addition, due to the mentioned Contactins involvement in myelination [ 55 , 89 , 103 , 104 ], changes in their expression may also concern disorders of myelinated axons and therefore of nerve conduction velocities [ 105 ]. In this context, besides the described effects on the neuronal lineage, in the present study, specific consequences were also demonstrated on the glial lineage by using a glia-specific marker as the GFAP, whose expression underwent a significant increase in the course of the disorder, thus justifying that a glia upregulation accompanied the observed neuronal degenerative phenotype, confirming the simultaneous activation of a neurorepair mechanism [ 56 , 57 , 66 , 67 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that Cntnap1 deficiency delays neuronal migration during perinatal cortical development. The binding of contactin to CNTNAP1 in cis interactions in the plasma membrane is required for developmental events such as neurite growth, neural cell adhesion, myelination, and neuronal migration (19,38,39). In Cntn1-KO mice, axonal guidance and dendritic projections in granule cells are defective (40).…”
Section: Figure 2 D1140y and G1251r Expression Levels In 293t Cells mentioning
confidence: 99%
“…CNTNAP1 is highly expressed in radial glial cells (RGCs) in the early neurogenic period and plays a decisive role in the timing of neuron and astrocyte generation (12). CNTNAP1 has also been found to bind Cntn1 (13,14), neurofascin (2,15,16), and native prion protein (17), which are involved in neurite outgrowth (18), neuronal migration (19), dendritic branching (20,21), and synaptogenesis (22), thereby allowing inferences about its potential functions in early brain development.…”
Section: Introductionmentioning
confidence: 99%